Assessing the COVID-19 impacts on the coffee industry in Laos: An input–output modelling approach - Somvang Phimmavong; Rodney J. Keenan; Viengvilay Phimmavong; Jerry Maroulis; Tek Narayan Maraseni (Cogent Economics & Finance, 2023)
This paper employs an input-output modelling approach to quantify the impact of decreases in coffee exports between 2019 and 2020 resulting from the implementation of various COVID-19 policies in Lao PDR. The analysis was undertaken at two levels in investigating the effects of these policies on (1) the regional economy in the main coffee producing region of Champasak Province in Southern Laos, and (2) the national economy of Lao PDR. Results were rather mixed at both the regional and national levels, for four reasons: (1) reduced production in other countries increased demand for green bean exports, resulting in a 1.8% (US\12 million) increase in the total value of gross outputs of the provincial economy; (2) reduced local demand and declines in processed coffee consumption and export in the food industry sector, resulted in a 1.5% decrease (US\10 million) in gross provincial production; (3) at the national level, more green bean exports increased the gross production output of the economy by 0.2% (US\24 million) while reduced processed coffee in food industry exports led to a reduction in gross production of 0.13% (US\19.6 million); and (4) the overall effects of COVID-19 restrictions are potentially positive for the coffee sector in Lao PDR in the short term but may have longer-term implications for the coffee sector due to shift away from processed coffee exports to green beans. Future policies to mitigate the impact of COVID-19 will be instrumental in stimulating investment and enhancing the benefits for the coffee sector in Laos.
Keywords: 330; COVID-19; coffee; input-output analysis; crop sector; food sector; Laos